Intake of various food groups among girls and boys with different utilisation of school meals - Moosburger, Ramona; Lehmann, Franziska; Haftenberger, Marjolein; Richter, Almut; Patelakis, Eleni; Mensink, Gert B. M. (DEU, 2022)
Children and adolescents spend a large part of their time at school, which is why the quality of school meals is of great importance. In this study, the extent to which intakes of various food groups among children and adolescents were in line with the recommendations of the Optimised Mixed Diet (OMD) were examined according to frequency of utilisation of school meals, based on data from the second Eating study as a KiGGS Module (EsKiMo II). Among 6- to 11-year-old boys, more frequent (≥ three times weekly) utilisation of school meals is associated with more frequently meeting or exceeding the OMD recommendation for fruit consumption. The same is true among 12- to 17-year-old girls for eggs and fats/oils used for cooking or spreads, and among 12- to 17-year-old boys for fish. The results from EsKiMo II show that regular uptake of school meals is associated with differences in intakes of various food groups with respect to the OMD recommendations.